Effects of climate change on hydrological planning: Proposal actions in the Guadalhorce River Basin / Efectos del cambio climático en la planificación hidrológica: propuesta de actuación en la cuenca del rÃo Guadalhorce - Jiménez-Fernández, Pedro; Jimenez-Madrid, Alberto; Gemár, German (Tecnología y ciencias del agua, 2019)
The Fifth Assessment Report from the Intergovernmental Panel on Climate Change estimates an increase in average temperatures and a 10–20% precipitation decrease for the Mediterranean region, which will likely generate drought events in the Guadalorce River watershed. This study attempts to determinate the potential impacts that climate change may have on water resources. The Guadalhorce River basin is the most important in Malaga (southern region of Spain) and supplies water to more than 10 000 ha of crops and Malaga city. The degree to which climate change-driven droughts will alter water resource supplies and demands were evaluated. Resulting social and environmental implications were also determined.